2014
DOI: 10.1007/s10654-014-9884-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between serum biomarkers of lipid metabolism and overall, breast and prostate cancer risk

Abstract: Experimental studies provided evidence about mechanisms by which cholesterol, especially high density lipoprotein cholesterol (HDL-C), could influence carcinogenesis, notably through antioxidant and anti-inflammatory properties. However, prospective studies that investigated the associations between specific lipid metabolism biomarkers and cancer risk provided inconsistent results. The objective was to investigate the prospective associations between total cholesterol (T-C), HDL-C, low density lipoprotein chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
145
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(154 citation statements)
references
References 44 publications
7
145
2
Order By: Relevance
“…Cancer Epidemiol Biomarkers Prev; 24(7) July 2015 Cancer Epidemiology, Biomarkers & Preventionand 10 cohort studies) were included in this analysis (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In the 14 included studies, the retrospective cohort study by Farwell and colleagues (18) was also included because it prospectively measured serum cholesterol levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer Epidemiol Biomarkers Prev; 24(7) July 2015 Cancer Epidemiology, Biomarkers & Preventionand 10 cohort studies) were included in this analysis (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In the 14 included studies, the retrospective cohort study by Farwell and colleagues (18) was also included because it prospectively measured serum cholesterol levels.…”
Section: Resultsmentioning
confidence: 99%
“…Some epidemiologic studies and preclinical models also suggest that high levels of cholesterol in blood may be associated with the risk of prostate cancer (6). However, the findings from these epidemiologic studies are inconsistent (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), as some studies have reported that high levels of cholesterol increased risk of prostate cancer (15,16,18), and some studies have reported no association between cholesterol and risk of prostate cancer (10-14, 17, 19, 21-23). Moreover, high cholesterol has been proposed to be closely associated to late-stage prostate cancer, and cholesterol may play a promotional role in late-stage prostate cancer development and progression (11,15,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, numerous reports have focused on the role of apoA1 in breast cancer, but extremely diverse conclusions were drawn. A prospective study based on 7557 subjects [45] declared that the serum level of apoA1 was inversely associated with breast cancer risk, contrary to a recent publication by Martin [46]. Furthermore, a study has indicated that breast cancer cells with elevated apoA1 level were more sensitive to chemotherapy than cells with lower apoA1 level [47].…”
Section: Discussionmentioning
confidence: 99%
“…While epidemiologic evidence does not support an association between serum cholesterol levels and risk of total PC [8, 9], there is a suggestion that elevated cholesterol may be associated with increased risk of aggressive disease [8, 1012], although not all studies have reported this finding [9, 1315]. There is mixed evidence for an association between serum cholesterol levels and risk of PC progression, with some studies reporting positive associations between elevated cholesterol and risk of PC recurrence [16] and mortality [17, 18], while another study reported no association with risk of PC mortality [19].…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies examined the association between cholesterol subfractions —low and high density lipoprotein (LDL and HDL, respectively) — and PC. While there is some evidence that elevated LDL [12, 20] and low HDL [10, 21] are associated with increased risk of aggressive PC, not all studies reported these findings [13, 15, 22], and the association between cholesterol subfractions and risk of PC recurrence has not been widely studied. Finally, evidence for an association between serum triglycerides and PC recurrence is mixed [14, 23].…”
Section: Introductionmentioning
confidence: 99%